Post-Conviction Review on Trial: when do Appellate Courts Correct for Prosecutorial Misconduct? - Scheuerman, Heather (Crime & delinquency, 2023)
Appellate courts sometimes provide relief in cases where prosecutors engage in certain actions, either free from scrutiny during investigation (backstage) or under judicial oversight during litigation (front-stage), that go beyond their authority and the law. Yet little is known about how the nature and types of prosecutorial misconduct recognized by appellate courts systematically affect their decisions to provide relief. Using data from the Center for Prosecutor Integrity, we analyze 150 appellate court cases between 2010 and 2015 in which prosecutorial misconduct is substantiated by the courts. We find that higher courts are more likely to correct for cases involving multiple types of misconduct and for cases in which the misconduct occurs ?backstage,? outside of judicial oversight, rather than during litigation.